Carbon in sediment cores from the Western Irish Sea Mud Belt, June 2022 - Hannah C Muir; Claire Evans; Kate Peel (PANGAEA, 2025)
Sediment cores were split lengthwise using a Geotek core splitter at the British Ocean Sediment Core Research Facility (BOSCORF). A U-channel of known volume was used to extract samples from the centre of each core at depth intervals: every 2 cm for the top 20 cm of the sediment core, every 5 cm between 20–50 cm, and every 10 cm beyond 50 cm. Samples were freeze-dried and homogenised, and both wet and dry weights were recorded before analysis. Sediment dry bulk densities were estimated by dividing the mass of dry sediment (g) by the original volume of sediment sampled (cm3). The organic carbon and total carbon concentrations were measured using a Flash 2000 Elemental Analyser. The inorganic carbon was removed via acid fumigation before organic carbon analysis. Sediment carbon density (SCD, gC/cm3) was estimated by multiplying the sediment organic carbon concentration (%) by the sediment dry bulk density (g/cm3).
In: Muir, Hannah C; Reading, David G; Warwick, Phillip E; Peel, Kate; Evans, Claire (2025): Sediment core data (organic carbon, dry bulk density, grain size, radionuclide) from the Western Irish Sea Mud Belt June 2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983345